Broiler farms practice without AGP as an Islamic conceptionin the strategy to achieve “asuh” food - Hafsan, Hafsan; Kiramang, Khaerani; Thaha, Aminah Hajah; Rasyid, Muhammad Rusdi (Journal of Islam and Science, 2021)
The use of Antibiotics Growth Promoters (AGP) was once a reliance for Broiler farms that aim to improve immunity as well as trigger the growth of broiler. It turned out that the use of AGP elicit a variety of very harmful impacts on human’s health, the presence of residues of antibiotics in broiler meat will reduce resistance of humans who consume them to some types of antibiotics even antibiotics that are prepared to handle the case of multi-resistant bacteria, namely the presence of antibiotic residues in broiler meat that will reduce the resistance of humans who consume them. So no longer impervious to some antibiotics even antibiotics that are prepared to handle the case of multi-resistant bacteria. This has become a limiting factor for the community, especially Muslims who are required to consume foods that are not only halal but bring benefits and do not contain harmful substances as admonitions in the Quran and hadith. This reality requires options to solve problems and answer real problems in people's lives wisely and contextually. Although AGP is required by the broiler, but based on many research results have shown that its role can be substituted with the addition of feed additives such as probiotics, enzymes and herbs as feed quality improvement efforts, included the implementation of biosecurity which must be carried out in an integrated manner. Broiler farms that implement good industry management has proved able to guarantee the availability of broiler as a source of animal protein is Safe, Healthy, and Whole Halal (in the Indonesian acronym is ASUH) and has a wide market share. This context be in accordance to the conception of food safety in Islam, food safety from the Islamic normative context namely halal and food safety from the health aspect, namely Thayyib. This paper responds to the issue of food safety which has been a fidgetiness for all stratums of Muslim society, whereas the ASUH food source is one of the fulfilments of the main points of the Maqasid al-Shari'ah or the general objective stipulated in Islamic law, namely to realize goodness, provide benefits and avoid damage to humans.